Mesenchymal Stem Cells for the Treatment of Spinal Arthrodesis: From Preclinical Research to Clinical Scenario. (13th February 2017) - Salamanna, F.; Sartori, M.; Brodano, G. Barbanti; Griffoni, C.; Martini, L.; Boriani, S.; Fini, M.
Abstract : The use of spinal fusion procedures has rapidly augmented over the last decades and although autogenous bone graft is the "gold standard" for these procedures, alternatives to its use have been investigated over many years. A number of emerging strategies as well as tissue engineering with mesenchymal stem cells (MSCs) have been planned to enhance spinal fusion rate. This descriptive systematic literature review summarizes the in vivo studies, dealing with the use of MSCs in spinal arthrodesis surgery and the state of the art in clinical applications. The review has yielded promising evidence supporting the use of MSCs as a cell-based therapy in spinal fusion procedures, thus representing a suitable biological approach able to reduce the high cost of osteoinductive factors as well as the high dose needed to induce bone formation. Nevertheless, despite the fact that MSCs therapy is an interesting and important opportunity of research, in this review it was detected that there are still doubts about the optimal cell concentration and delivery method as well as the ideal implantation techniques and the type of scaffolds for cell delivery. Thus, further inquiry is necessary to carefully evaluate the clinical safety and efficacy of MSCs use in spine fusion.